2013
DOI: 10.1159/000350726
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Cell Senescence Combine to Cause Maximal Renal Tubular Epithelial Cell Dysfunction and Loss in an in vitro Model of Kidney Disease

Abstract: Background: The incidence and cost of chronic kidney disease (CKD) are increasing. Renal tubular epithelial cell dysfunction and attrition, involving increased apoptosis and cell senescence, are central to the pathogenesis of CKD. The aim here was to use an in vitro model to investigate the separate and cumulative effects of oxidative stress, mitochondrial dysfunction and cell senescence in promoting loss of renal mass. Methods: Human kidney tubular epithelial cells (HK2) were treated with moderate hydrogen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 60 publications
1
39
0
1
Order By: Relevance
“…CKD is characterized by a continuous reduction in structural and functional decline in the kidney function that involves increased inflammation and oxidative stress, and reduced antioxidant capacity (Small et al, 2012b). The objective of this study was to assess the were injured with oxidative stress and then increased with use of the extracts, and we believe this also helps mediate cell survival in this model (Sanchez-Capelo, 2005), but the pro-fibrotic role of…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CKD is characterized by a continuous reduction in structural and functional decline in the kidney function that involves increased inflammation and oxidative stress, and reduced antioxidant capacity (Small et al, 2012b). The objective of this study was to assess the were injured with oxidative stress and then increased with use of the extracts, and we believe this also helps mediate cell survival in this model (Sanchez-Capelo, 2005), but the pro-fibrotic role of…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress inducedapoptosis is well-documented and manifests in renal pathologies as kidney atrophy and reduced kidney function (Small et al, 2012b). and inhibited Bcl-X L in kidney cells (Cuttle et al, 2001;Gao et al, 2012) and cancer (HeLa) cells (Singh et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study showed that cell senescence induces renal tubular epithelial cell dysfunction and loss in the model of renal disease. 47) It is also reported that cell senescence could contribute to organ aging and the expression of senescence-associated genes are enhanced in aging kidney. 48) These results provide evidence towards the effect of ROS and cell senescence in renal damage, as we show in Fig.…”
Section: Hfd and Hg Culture Comparisonmentioning
confidence: 99%
“…Most of all, pediatric nephrolithiasis presents increasing morbidity for the past several decades, meanwhile, a concomitant alarming rise in health care costs and burden to the children population suffering this disease [26]. Increasing evidence shows that the ERK signaling pathway and RTEC dysfunction and attrition are central to the pathogenesis of kidney diseases [9,27]. MUC4 is reported as an activator of ERK signaling pathway in epithelial cells [28].…”
Section: Discussionmentioning
confidence: 99%